2011
DOI: 10.1155/2011/578097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Secretory Protein C1qTNF6, a C1qTNF Family Member, in Hepatocellular Carcinoma

Abstract: Background: Recent studies have revealed that the adiponectin-associated protein belonging to the C1qTNF family mediates various biological processes. However, the pathobiological property of C1qTNF6 in carcinogenesis remains unclear. Here, we investigated the expression status of C1qTNF6 in human hepatocellular carcinomas and subsequently attempted to determine the role of C1qTNF6 in tumor neovascularization. Methods: Immunohistochemical staining was performed to evaluate the expression of C1qTNF6 in hepatoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…The detailed procedure of the xenograft assay is described previously (Takeuchi et al . ,b). The length and width of the tumours were measured using a caliper with a precision of 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedure of the xenograft assay is described previously (Takeuchi et al . ,b). The length and width of the tumours were measured using a caliper with a precision of 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…For stable expression of Nedd4L in A2058 cells, a previously described Nedd4L‐expression vector (Takeuchi et al . ,b) was modified to express the product of the neomycin‐resistant gene and transfected into cells using N ‐[1‐(2,3‐dioleoyloxy) propyl]‐ N , N , N ‐trimethylammonium methylsulphate (DOTAP) transfection reagents (Boehringer Mannheim, Indianapolis, IN, USA) according to the manufacturer's protocol. Briefly, A2058 cells were seeded at approximately 50% confluency in 10‐cm culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…An immunohistochemistry assay indicated that c1QTNF6 is mainly localized in hepatocellular carcinoma cells and endothelial cells in tumor tissues. High expression of c1QTNF6 was revealed to activate the Akt signaling pathway, increase tumor angiogenesis and reduce the necrosis of HepG2 cells (12). c1QTNF6-interference was revealed to inhibit the Erk1/2 signaling pathway in 3T3-L1 adipocytes (13).…”
Section: Introductionmentioning
confidence: 99%
“…C1qTNF-related protein-6 (CTRP6) is also a C1qTNF family member that consists of a signal peptide, a short variable region, a collagen-like region, and a C-terminal globular domain, and is thought to play a role in fatty acid metabolism (Kishore et al, 2004), hepatocellular carcinoma (Takeuchi et al, 2011), and immune response . A recent study provides evidence that CTRP6 was found in serum and its expression in fat tissues was enhanced in obese, ob/ob and adiponectin null-mice.…”
Section: Introductionmentioning
confidence: 99%